Neuroendocrine Dysfunction in Fibromyalgia - Özlem Altındağ (Archives of Rheumatology, 2009)
Fibromyalgia is a chronic rheumatismal disease characterized by widespread pain and fatigue with unknown etiology. Subtle alterations of the neuroendocrine system in fibromyalgia syndrome have been proposed as a shared pathway linking numerous etiological and perpetuating processes with symptoms and observed physiological abnormalities. The role of neurohormonal mechanisms in the pathogenesis of fibromyalgia is discussed in this paper. (Turk J Rheumatol 2009; 24: 98-102)